Role of Salicyic acid in induction systemic acquired resistance in Cucurbita pepo plant against Zucchini yellow mosaic virus. - Raie, Saleem; Ahmad, Ahmad; Ahmad, Hassan (Latakia University Journal -Biological Sciences Series, 2018)
to studay the effect of salicylic acid (SA) in induction systemic acquired resistance (SAR) in Cucurbita pepo plants against Zucchini yellow mosaic virus, Cucurbita pepo plants were treated by three concentrations of SA (2, 1and 0.5 mM ) at two methodes spray and irrigation , three days post incolation in spring 2016 in Tartous covernorate. SAR evaluated through:Time delay of appearance of virus symptomes caused by virus, disease severity, percentage of dwarf of plant, yield, concentration of SA in plant and peroxidase activity POX. Results showed important role of SA in induction systemic resistance against ZYMV infection, where delyed of appearance of virus symptomes to 21 dayes, decreased disease severity to 2.8%, decreased percentage of dwarf of plant to 20.86%, improved yield of infected plants to 1415 gram,increased SA concentration in plants to 132.28 ppm and increased peroxidase activety to 0.362 nM,comparable with results of infected control (11days, 32.6%, 55.35%, 543gram, 17.38 ppm, 0.116 nM) respectively. Treatment by 2mM concentration gives better results in all later indicators, Followed by 1Mm concentration and finally 0.5 mM . Results of treatment at spray method was better than at irrigation. دور حمض الساليسيليك في تحريض المقاومة الجهازية في نبات الكوسا ضد العدوى بفيروس الموزاييك الأصفر في الكوسا Zucchini yellow mosaic virus. درس تأثير حمض الساليسيليك SA في تحريض المقاومة الجهازية المكتسبة SAR في نبات الكوسا تجاه فيروس الموزاييك الأصفر في الكوسا Zucchini yellow mosaic virus، تمت معاملة نباتات الكوسا بثلاثة تراكيز 2 و 1 و0.5 ميلي مول من حمض الساليسيليك بطريقتي الرش والري قبل العدوى بالفيروس بثلاثة أيام في ربيع 2016 في محافظة طرطوس. قُيّمت المقاومة الجهازية من خلال: موعد ظهور أعراض الاصابة بالفيروس، الشدة المرضية ، معدل تقزم النبات، تقدير الانتاجية، تركيز حمض الساليسيليك في النبات و نشاط أنزيم البيروكسيداز. أظهرت النتائج الدور الهام لحمض الساليسيليك في تحريض المقاومة الجهازية ، حيث أخرّ ظهور أعراض العدوى الفيروسية حتى 21 يوماً وخفَض شدة الاصابة حتى 2.8% وخفضّ معدل التقزم حتى20.86 % وتحسنّ انتاج النباتات المعداة من الثمار الى 1415غرام. وازداد تركيز حمض الساليسيليك في النبات حتى ppm132.28 وازداد نشاط أنزيم البيروكسيداز الى 0.362 نانومول، وذلك مقارنة مع قراءات الشاهد المعدى (11 يوماً، 32.6% ، 55.35% ، 543 غ، 17.38ppm، 0.116 نانومول) على التوالي.وأعطت المعاملة بالتركيز 2 ميلي مول أفضل النتائج في جميع المعايير السابقة، يليه التركيز 1 ميلي مول ثم التركيز 0.5 ميلي مول، وكانت نتائج المعاملة بطريقة الرش أفضل من طريقة الري.